Steinmetzite, Zn2Fe3+(PO4)2(OH)·3H2O, a new mineral formed from alteration of phosphophyllite at the Hagendorf Süd pegmatite, Bavaria. (2nd January 2018) - Grey, I. E.; Keck, E.; Kampf, A. R.; Mumme, W. G.; Macrae, C. M.; Gable, R. W.; Glenn, A. M.; Davidson, C. J.
Abstract: Steinmetzite, ideally Zn2 Fe 3+ (PO4 )2 (OH)·3H2 O, is a new mineral from the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Steinmetzite was found in a highly oxidized zone of the Cornelia mine at Hagendorf-Süd. It has formed by alteration of phosphophyllite, involving oxidation of the iron and some replacement of Zn by Fe. Steinmetzite lamellae co-exist with an amorphous Fe-rich phosphate in pseudomorphed phosphophyllite crystals. The lamellae are only a few μm thick and with maximum dimension ∼50 μm. The phosphophyllite pseudomorphs have a milky opaque appearance, often with a glazed yellow to orange weathering rind and with lengths ranging from sub-mm to 1 cm. Associated minerals are albite, apatite, chalcophanite, jahnsite, mitridatite, muscovite, quartz and wilhelmgümbelite.Goethite and cryptomelane are also abundant in the oxidized zone. The calculated density is 2.96 g cm –3 . Steinmetzite is biaxial (–) with measured refractive indices α = 1.642(2), β = 1.659 (calc.), γ = 1.660(2) (white light). 2V(meas) = 27(1)°; orientation is Y ≈b, X ^c ≈ 27°, with crystals flattened on 010 and elongated on [001]. Pleochroism shows shades of pale brown; Y > X ≈ Z . Electron microprobe analyses (average of seven crystals) with Fe reported as Fe2 O3 and with H2 O calculated from the structure gave ZnO 31.1, MnO 1.7, CaO 0.5, Fe2 O3 21.9, Al2 O3 0.3, P2 O5 32.9, H2 O 14.1 wt.%, total 102.5%. The empirical formula based on 2 P and 12 O, with all iron as ferric and OH–adjusted for charge balance is Zn1.65 Fe1.19 3+ Mn0.11 2+ Ca0.03 Al0.02 3+ (PO4 )2 (OH)1.21 ·2.79H2 O. The simplified formula is Zn2 Fe 3+ (PO4 )2 (OH)·3H2 O.Steinmetzite is triclinic, P 1̄, with unit-cell parameters: a = 10.438(2), b = 5.102(1), c = 10.546(2) Å, α = 91.37(2), β = 115.93(2) and γ = 94.20(2)°. V = 502.7(3) Å 3, Z = 2. The strongest lines in the powder X-ray diffraction pattern are [ d obs in Å ( I ) ( hkl )] 9.313(65) (100), 5.077(38) (010), 4.726(47) (002), 4.657(100) (200), 3.365 (55) (3̄02), 3.071(54) (11̄2) and 2.735(48) (3̄1̄2). The structure is related to that of phosphophyllite.